2013
DOI: 10.1080/08897077.2012.728990
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alcohol Use Patterns among Spanish-Speaking Patients

Abstract: Objective To assess drinking patterns of Spanish-speaking patients using a bilingual Computerized Alcohol Screening and brief Intervention (CASI) tablet computer equipped with the Alcohol Use Disorders Identification Test (AUDIT). Methods This retrospective study was conducted in a tertiary university hospital emergency department (ED) between 2006 and 2010. Data from 1,816 Spanish-speaking ED patients was analyzed using descriptive statistics, the chi-square test for independence, and the Kruskal-Wallis ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Studies showed that CASI was effective at identifying at-risk and consistent-with-dependency drinkers in less than 7 minutes, and demonstrated good acceptability by patients. It can be implemented in bilingual settings (English and Spanish) with minimal time commitment, and has shown to be an effective tool among the Spanish-speaking population in the ED 8,9. A follow-up study by Vaca et al10 supported the use of such SBIRT systems as holding “promise as a viable screening and intervention modality for a wide range of emergency department patients,” with up to 47% reduction in drinking amongst at-risk patients, 6 months afterwards.…”
Section: Methodsmentioning
confidence: 99%
“…Studies showed that CASI was effective at identifying at-risk and consistent-with-dependency drinkers in less than 7 minutes, and demonstrated good acceptability by patients. It can be implemented in bilingual settings (English and Spanish) with minimal time commitment, and has shown to be an effective tool among the Spanish-speaking population in the ED 8,9. A follow-up study by Vaca et al10 supported the use of such SBIRT systems as holding “promise as a viable screening and intervention modality for a wide range of emergency department patients,” with up to 47% reduction in drinking amongst at-risk patients, 6 months afterwards.…”
Section: Methodsmentioning
confidence: 99%
“…It is important that future studies of alcohol SBI also address the developmental and demographic differences (ethnicity, race, and age) among populations 1320. For example, studies have shown important differences between black and white youths' motivation to consume alcohol 2122.…”
Section: Commentarymentioning
confidence: 99%
“…According to Cooper et al21, coping motives (to reduce negative emotions) played a bigger role in black youth, and enhancement motives (to augment positive emotional states) were a greater role in white youth. Even though research is greatly lacking within the Latino and non-English speaking populations, some studies indicate significant differences in alcohol use among English- and Spanish-speaking patients 81317…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of alcohol use and alcohol-related injuries have identified several gender and age-related trends in consumption patterns [ 6 , 7 ]. Men and older adults are also more likely to report higher rates of alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%